2014
DOI: 10.1109/tmtt.2014.2315594
|View full text |Cite
|
Sign up to set email alerts
|

The Unified-FFT Algorithm for Fast Electromagnetic Analysis of Planar Integrated Circuits Printed on Layered Media Inside a Rectangular Enclosure

Abstract: The unified fast Fourier transform (UFFT) methodology is proposed for fast method of moments analysis of dense integrated circuits embedded in layered media inside perfectly electric conducting or perfectly magnetic conducting enclosures of rectangular cross section. The pre-corrected fast Fourier transform (FFT) method is modified to handle the dyadic Green's function (DGF) of shielded layered media through factorization of the DGF into four convolution/correlation terms enabling fast matrix solve operations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 38 publications
0
19
0
Order By: Relevance
“…In addition to those in [5], there is further noteworthy work. FFTs have been used to increase parallelization of MLFMA with the MLFMA-FFT method [11], and a similar application to GPU clusters [12].…”
Section: Introductionmentioning
confidence: 95%
See 4 more Smart Citations
“…In addition to those in [5], there is further noteworthy work. FFTs have been used to increase parallelization of MLFMA with the MLFMA-FFT method [11], and a similar application to GPU clusters [12].…”
Section: Introductionmentioning
confidence: 95%
“…A brief review of relevant and/or similar work can be found in [5]. In addition to those in [5], there is further noteworthy work.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations